Iron-rich solar particle events measured by SOHO/ERNE during two solar cycles - O. Raukunen; E. Valtonen; R. Vainio (EDP Sciences, 2022)
Aims. We study the differences in the heavy ion composition of solar energetic particle (SEP) events between solar cycles 23 and 24.
Methods. We have surveyed the SOHO/ERNE heavy ion data from the beginning of solar cycle 23 until the end of June 2015, that is, well into the declining phase of cycle 24. We used this long observation period to study the properties of heavy ions (from C to Fe) and to compare the two solar cycles in this respect. We surveyed the data for SEP events with enhancements in the Fe/C and Fe/O intensity ratios in the energy range 5–15 MeV per nucleon, and associated the events with solar flare and coronal mass ejections (CME) when possible. We studied the properties of heavy ions in these events and compared the average relative abundances of heavy ions between the two solar cycles.
Results. We found that fewer days had C and O intensities higher than ~10 -3 cm-2 sr-1 s-1 (MeVn-1)-1 during solar cycle 24 than during cycle 23. For Fe this difference was clear even at lower intensities. We also found that fewer days had Fe/(C+O) > 0.183 during cycle 24. We identified 86 SEP events with at least one Fe-rich day, 65 of which occurred during cycle 23 and only 21 during cycle 24. We found that impulsive events have been almost completely absent during cycle 24. Mean abundances of heavy ions in the events were found to be significantly lower during cycle 24 than in cycle 23. Our results reflect the reduced solar activity in cycle 24 and indicate lower efficiency of particle acceleration processes for both gradual and impulsive SEP events in cycle 24.